Sintesis dan Karakterisasi Fotokatalis TiO2/Zn dengan Asam Askorbat Sebagai Reduktor - Anastasya, Wulanda; Suryani, Okta (Periodic, 2024)
Hydrogen gas (H2) is a promising alternative energy source compared to fossil fuels because it is abundant, highly efficient, non-toxic, and produces no harmful emissions when used as fuel. H2 gas can be produced with a simple, inexpensive, and environmentally friendly process, for example through photocatalytic water splitting by photocatalysts with the help of sunlight. One of the semiconductors as a photocatalyst can absorb sunlight for photocatalytic water splitting is TiO2. In this study, TiO2 has been synthesized whose morphological structure has been modified (Hierarchical Porous TiO2) and doped with Zn metal to reduce the band gap. Hierarchical Porous TiO2 (HPT) has been successfully synthesized. XRD characterization was used  to determine the structure and particle size. HPT has an anatase crystal structure with an average particle size of 19.24 nm. HPT has an energy band gap of  3.25 eV. Then doping with Zn metal reduce the band gap to 2.91 eV. Metal doping is proven to be able to increase the light absorption of HPT from 300 nm to 600 nm in the visible light region. Characterization results show that Zn doping is able to reduce the band gap of HPT semiconductor photocatalyst.